STATE OF THE RESEARCH IN NURSING IX TH REGION OF THE ARAUCANIA, TEMUCO, CHILE 2002 - Rivas Riveros, Edith Elina; Osorio Spuler, Ximena (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The development of the investigation projected us in nurse’s image that we want for the XXI Century and the positioning that we will have. This image will be characterized by interventions that demonstrate scientific quality and humanization of the care. The practices of the care, although they are conceived as a practical activity, they need of the intellectual activity and of a critical mass of investigators and ideologists that guide the actions, situation that should be based in the evidence. The purpose of the investigation was to identify through a descriptive, exploratory study, correlation the state of the investigation in Infirmary in the IX Region of the Araucania, Chile. The specific objectives were: to analyze the conditions in that you development the improvement of the nurses in the IX Region and to contribute to identify the investigation lines. The study picks up the characteristics in that the improvement of the nurses is developed in the IX Region, Chile: Degree, Magíster and Doctorates until the year 2002. One concludes that as for approaches the positivist prevails, the motivation of the Nurses to there be perfecting in programs of postdegree this one given fundamentally by personal development and to help to improve the profession; those who realize studies of postdegrees get out of a jam themselves in teaching in institutes and / or universities and the subject matter of the investigations is fundamentally orientated towards the education of nursing.